COLLABORATIVE TRANSLATION AND STUDENT ENGAGEMENT: A MIXED-METHODS STUDY IN INDONESIAN HIGHER EDUCATION - Erika Sinambela; Lastri Wahyuni Manurung; Carolina Carolina; Indah Rizki Yuliani (English Education Department at FKIP Nommensen University, 2026)
This study investigates the effectiveness of collaborative translation in enhancing student engagement and language development in translator education. The research addresses three questions: (1) how collaborative translation influences student engagement, (2) to what extent it improves language proficiency, and (3) what factors affect its effectiveness in classroom practice. Using a mixed-methods design, the study involved 20 sixth-semester students in an English Literature program at HKBP Nommensen University. Data were collected through classroom observations, a five-item Likert-scale questionnaire, semi-structured interviews, and pre- and post-tests assessing vocabulary, grammar, and translation accuracy. Quantitative data were analyzed descriptively using mean comparisons, while qualitative data were examined through thematic analysis and triangulation across data sources. Results showed consistent improvement in language performance, with mean scores increasing from 68 to 80 in vocabulary, 70 to 82 in grammar, and 65 to 78 in translation accuracy, indicating moderate learning gains. Questionnaire and interview findings revealed increased participation, shared responsibility, and greater confidence during collaborative tasks. The effectiveness of the project was influenced by group interaction, lecturer feedback, student motivation, and the use of digital resources. Participation was voluntary, and informed consent was obtained from all participants. The findings suggest that collaborative translation supports process-oriented and socially mediated translation learning.